Influence Of Corporate Social Responsibility, Board Of Commissioners, Board Of Director And Audit Committee On Financial Performance With Profit Management As A Moderating Variable In Listed Manufacturing Companies On The Indonesia Stock Exchange ( Idx) - Nurul Aulia Sani; Erlina; Sirojuzilam (Jurnal Mantik, 2022)
This study aims to examine and analyze the effect of corporate social responsibility, the board of commissioners, the board of directors, the audit committee on financial performance with earnings management as the moderating variable. The population in this study were 171 manufacturing companies listed on the Indonesian stock exchange for the period 2010-2019, with The sampling technique was purposive sampling so that 35 samples were obtained. The data analysis method used multiple linear regression analysis and interaction test with the help of the Eviews application program. The results show that CSR, the board of commissioners and the audit committee partially have a positive effect on financial performance, while the board of directors partially has no effect on financial performance. Simultaneously CSR, the board of commissioners, the board of directors and the audit committee simultaneously have a significant effect on financial performance Earnings management as a moderating variable is able to moderate the influence of the audit committee simultaneously has a significant effect on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange for the 2010-2019 period . The moderating variable is not able to moderate the influence of CSR, the board of commissioners and the board of directors simultaneously have a significant effect on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange for the 2010-2019 period